2015
DOI: 10.3109/09637486.2015.1056108
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins in purple and blue wheat grains and in resulting bread: quantity, composition, and thermal stability

Abstract: The anthocyanin composition of blue (Triticum aestivum L., cv. Skorpion) and purple wheat (Triticum aethiopicum JAKUBZ cv. Abyssinskaja arrasajta cv. Abyssinskaja arrasajta), cultivated in the Czech Republic, and of the prepared whole blue and purple wheat bread was determined. In blue and purple wheat, 19 and 26 anthocyanins, respectively, were tentatively identified by liquid chromatography and mass spectrometry. The total content of anthocyanins determined in blue and purple wheat was 9.26 and 13.23 mgkg(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 28 publications
3
31
1
5
Order By: Relevance
“…For example, retention of malvidin in the bun and biscuit after baking were 95.9% and 98.6%, respectively as reported by Karakaya et al [ 29 ]. Similarly, a significant decrease ranging from 37.5% to 70% in the TAC content was determined during snack production by Nemś et al [ 30 ], whereas Barti et al [ 31 ] found a decrease in the anthocyanin content of breads produced using purple and blue wheat flours during the baking process. As expected regarding the colorimetric parameters, a lower L * value was observed for S3, whereas a * and b * values suggested a red dark (S2) to red brown (S3) color, with a pleasant taste due to the presence of black rice.…”
Section: Resultsmentioning
confidence: 90%
“…For example, retention of malvidin in the bun and biscuit after baking were 95.9% and 98.6%, respectively as reported by Karakaya et al [ 29 ]. Similarly, a significant decrease ranging from 37.5% to 70% in the TAC content was determined during snack production by Nemś et al [ 30 ], whereas Barti et al [ 31 ] found a decrease in the anthocyanin content of breads produced using purple and blue wheat flours during the baking process. As expected regarding the colorimetric parameters, a lower L * value was observed for S3, whereas a * and b * values suggested a red dark (S2) to red brown (S3) color, with a pleasant taste due to the presence of black rice.…”
Section: Resultsmentioning
confidence: 90%
“…[2010] detected only Cy-3-Glu. In turn, using newly developed HPLC-MS method, Bartl et al [2015] managed to separate and defi ne 19 anthocyanins in the blue wheat and 26 in the purple wheat. As in the grain of popping maize, acylated forms of anthocyanins were dominant in the grain of purple wheat.…”
Section: Anthocyanins Profi Le Of Wheat Grainmentioning
confidence: 99%
“…In our study, the content of the dominant isomer of Cy-3-di-Mal-Glu, identifi ed in blue popping maize, was 113.50 μg/g d.m., while the content of its two isomers occurring at retention times of 15.63 and 16.19 min was 2.4 and 5.4 times lower, respectively. Although Bartl et al [2015] identifi ed a large number of anthocyanins in the grains of blue and purple wheat, they measured the low content of Cy-3--Glu in them, only at about 1.0 to 1.7 μg/g d.m. However, our results are comparable with the values obtained by Abdel-Aal et al [2006] for the content of Cy-3-Glu amounting to 20.3 μg/g d.m.…”
Section: Quantifi Cation Of Anthocyaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…These parameters were declared in the variety description presented by Martinek et al (2013b). Variety Scorpion is suitable for baking bread, since intake of anthocyanins may play an important role in the prevention of human diseases (Bartl et al 2015). Compared to control Ilona, the blue wheats showed good qualitative traits in term of protein as well as gluten content.…”
Section: Quantitative and Qualitative Traits Among And Within Colour mentioning
confidence: 99%